Identification of independent APP locus duplication in Japanese patients with early-onset Alzheimer disease. Issue 9 (14th August 2009) - Kasuga, K; Shimohata, T; Nishimura, A; Shiga, A; Mizuguchi, T; Tokunaga, J; Ohno, T; Miyashita, A; Kuwano, R; Matsumoto, N; Onodera, O; Nishizawa, M; et al.
Abstract : Background: The occurrence of duplications of the amyloid precursor protein gene ( APP ) has been described in European families with early-onset familial Alzheimer disease (EO-FAD) and cerebral amyloid angiopathy. However, the contribution of APP duplication to the development of AD in other ethnic populations remains undetermined. Methods: The occurrence of APP duplication in probands from 25 families with FAD and 11 sporadic EO-AD cases in the Japanese population was examined by quantitative PCR and microarray-based comparative genomic hybridisation analyses. APP expression level was determined by real-time quantitative reverse-transcription (RT) PCR analysis using mRNA extracted from the peripheral blood of the patients. Results: We identified APP locus duplications in two unrelated EO-FAD families. The duplicated genomic regions in two patients of these families differed from each other. No APP duplication was found in the late-onset FAD families or sporadic EO-AD patients. The patients with APP duplication developed insidious memory disturbance in their fifties without intracerebral haemorrhage and epilepsy. Quantitative RT-PCR analysis showed the increased APP mRNA expression levels in these patients compared with those in age- and sex-matched controls. Conclusions: Our results suggest that APP duplication should be considered in patients with EO-FAD in various ethnic groups, and that increased APP mRNA expression level owing to APP duplication contributes to AD development.